Creation of a Model Society through Epic Reading - D.S, Ms. Padmaja; Jairam, Dr. Rajani (IJRDO - Journal of Social Science and Humanities Research, 2016)
A subhashita (Sanskrit: सुभाषित) is a literary genre of Sanskrit epigrammatic poems and their message is an aphorism, maxim, advice, fact, truth, lesson orriddle. Su in Sanskrit means good; bhashita means spoken; which together literally means well-spoken or eloquent saying.Subhashitas are known for theirinherent moral and ethical advice, instructions in worldly wisdom and guidance in making righteous deeds. Subhashitas create an appeal as the inherent message is conveyed through poems which quote practical examples which are often rhythmic in nature. The subhashita deals with various subjects and includes topics of day to day Experiences that everyone can easily relate to.A subhashita is always eloquent in form, structured in a poetical form, complete in itself and concisely depicts a single emotion, idea, righteousness, truth or situation.Subhāşitas act as teacher in formulating the sense of morality and character, which sums up the total of a person’s virtues including dispositions, behaviors, habits, likes, dislikes, capacities, traits, ideals, ideas, values, feelings, and intuitions. They are drawn from real life observations or situations with a sympathetic understanding of human impulses and behavior. While some may reflect the state of affairs of the society at the time they were composed; in general the wisdom they espouse is timeless. As such, they generally hold all that is good and true “till eternity.” A great strength of subhāşitas is their ability to provide comfort and hope in difficult times.